Effect of Synoptic‐Scale Dynamics on the Vertical Distribution of Tropospheric Ozone Over the Arabian Sea and the Indian Ocean During the Boreal Winter of 2018. Issue 20 (17th October 2022) - Satheesh Chandran, P. R.; Sunilkumar, S. V.; Muhsin, M.; Alladi, Hemanth Kumar
Abstract: Ozone (O3 ) and relative humidity profiles obtained from in situ electrochemical concentration cell ozonesonde‐radiosonde observations over the Arabian Sea and the Indian Ocean from 16 January to 14 February 2018 during the Integrated Campaign for Aerosols gases and Radiation Budget cruise were analyzed. On the basis of the prevailing synoptic conditions during the cruise period, the cruise track was divided into three legs which were studied separately. The main objective of this study was to investigate the influence of prevailing synoptic scale dynamics and transport on the vertical distribution of ozone in the troposphere, especially in the tropical tropopause layer (TTL) region. Tropospheric ozone exhibits pronounced latitude variations over the Arabian Sea and the Indian Ocean with very high values (∼60–70 ppbv) above the marine boundary layer near the Indian landmass. Distinct ozone‐rich plume‐like structures are observed in the free troposphere around 1–3 and 4–5 km. At around 1–3 km, the ozone plume was maintained by the continental outflows from the Indian sub‐continent. The mid‐tropospheric (4–5 km) high ozone‐low water vapor layer is hypothesized to be associated with the equatorward return flow of the Hadley circulation. Enhanced (declined) ozone is observed below 12 km altitude in the descending (ascending) branch of Hadley circulation. The ozone distribution in the TTL shows distinct structures associated with the prevailing synoptic dynamics and transport during respective legs. Evidences of stratospheric intrusion and air mass transport from biomass burning locations are seen regarding upper tropospheric ozone enhancements. Key Points: Continental outflow of polluted air caused the ozone rich plume structure around 1–3 km over the pristine oceanic region Mid‐tropospheric tongue of high ozone extending to the equator is hypothesized to be associated with the mean meridional circulation Significant ozone enhancement in the upper troposphere (50–60 ppbv) is associated with the western disturbance